The role of personal wealth in small business finance - Avery, Robert B.; Bostic, Raphael W.; Samolyk, Katherine A. (Journal of Banking & Finance, 1998)
This paper provides new empirical evidence on the relationship between personal commitments and the allocation of small business credit. The data suggest that personal commitments are important for firms seeking certain types of loans. Guarantees are more prevalent than collateral and organization type (corporate versus noncorporate status) appears to be particularly important in determining commitment use. No systematic relationship is observed between commitment use and owner wealth. Personal commitments appear to be substitutes for business collateral, at least for lines of credit, while personal collateral and personal guarantees do not seem to substitute for each other. Personal commitments have generally become more important to small business lending since the late 1980s.